Standing Pelvic Postures and Continence Ultrasonic Parameters in Women with and without Stress Urinary Incontinence - farideh dehghan manshadi; Javad Sarrafzadeh; Zinat Ghanbari; Anooshirvan Kazem Nejad; MahmoudReza Azghani; Mohamad Parnianpour (Vesnu Publications, 2014)
Introduction:  The effect of interventions in forms of changing body posture on Pelvic Floor Muscles (PFM) function is discussed in recent years. The present study was aimed to investigate the effects of changes in pelvic posture, also PFM and Transversus Abdominis Muscle (TrA) contractions on some continence ultrasonic parameters in women with and without Stress Urinary Incontinence (SUI). Materials and methods: Twenty-one women with SUI and twenty matched incontinent women, (mean age 42.7 and 39.2 years, respectively) were recruited to the study. We assessed some continence ultrasonic parameters via Trans Labial Ultrasonography (TLUS) in neutral standing position, during anterior and posterior pelvic tilt, PFM and TrA contractions. Shapiro-Wilk, Student t-test, Repeated measures ANOVA, Bonferroni post hoc paired comparisons, and Pearson tests were performed to analyze the data. The significance level was set as P < 0.05. Results: Regarding ultrasonic assessment, the main effect of intervention was significant on the angels of Alpha, Gamma and Levator plate (P < 0.05) with no significant effect on the Beta angle (P > 0.05). There was a significant difference in effect, of posterior pelvic tilt on Gamma and Levator plate angles between the two groups (P < 0.05). Anterior pelvic tilt resulted in an increase in Gamma angle in both groups ((P < 0.05). Conclusion: Posterior pelvic tilt results in changes in ultrasonic parameters towards increasing pelvic floor stability in comparison to the anterior pelvic tilt. Key Words: Pelvic Posture, Ultrasonography, Urinary Continence, Stress Urinary Incontinence.